Effect of sand versus grass training surfaces during an 8-week pre-season conditioning programme in team sport athletes - Binnie, M. J.; Dawson, B.; Arnot, M.; Pinnington, H.; Landers, G.; Peeling, P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: When compared to firmer and more traditional training venues such as grass, sand exercise is associated with a higher energy cost and lower impact-training stimulus (Impellizzeri et al., 2008; Pinnington & Dawson, 2001a; 2001b). There is recent evidence to suggest that sand training can be beneficial in a team sport training environment (Binnie et al., 2013a; 2013b), however there is limited research to show the long-term training impact. This study aimed to investigate the training benefits of sand versus grass surfaces, during an 8-week pre-season conditioning program in team sport athletes. Methods: Participants (n=24) were tested pre- and posttraining for leg strength and balance, vertical jump, agility, speed, repeat speed, and maximal oxygen consumption (VO2max). Heart rate (HR), training load (session-RPE), movement patterns (GPS), and perceptual measures were monitored throughout. Participants completed 2x1 h conditioning sessions per week on sand (SAND) or grass (GRASS) surfaces, incorporating interval training, sprint and agility drills, and small-sided games. Results: Significantly higher (p<0.05) HR and training load in the SAND versus GRASS group throughout each week of training, plus some moderate effect sizes to suggest lower perceptual ratings of soreness and fatigue on SAND. Significantly greater (p<0.05) improvements in VO2max were measured for SAND compared to GRASS. Conclusion: Substituting sand for grass training surfaces throughout an 8-week conditioning program can significantly increase the relative exercise intensity and training load, subsequently leading to superior improvements in aerobic fitness. Overall, using sand surfaces in a team sport pre-season training programme may allow for more optimal athlete preparation, by maximising the training response and reducing performance limiting effects that may arise from heavy training loads on firm surfaces.